1999
DOI: 10.4319/lo.1999.44.2.0440
|View full text |Cite
|
Sign up to set email alerts
|

The nutrient stoichiometry of benthic microalgal growth: Redfield proportions are optimal

Abstract: Abstract-Cellular nutrient ratios are often applied as indicators of nutrient limitation in phytoplankton studies, especially the so-called Redfield ratio. For periphyton, similar data are scarce. We investigated the changes in cellular C : N : P stoichiometry of benthic microalgae in response to different levels and types of nutrient limitation and a variety of abiotic conditions in laboratory experiments with natural inocula. C : N ratios increased with decreasing growth rate, irrespective of the limiting nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
174
3
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(190 citation statements)
references
References 20 publications
11
174
3
2
Order By: Relevance
“…8b) in the current study are similar to ratios (46-51) reported from Deception Bay in 2005 but are higher than the ratio (14) reported for Deception Bay in 1999-2000 (Watkinson et al 2005) and the Eastern Banks (16.4-22.4) (Ahern et al 2007). The N : P ratios reported in the present study, particularly during the incipient, rapid growth and plateau phases (47-72), were substantially higher than the various optimum N : P ranges published in the literature, including optimum ratios for unicellular phytoplankton (16) (Redfield et al 1963), freshwater periphyton (18) (Hecky et al 1993), medium ratio (30) for benthic plants (Atkinson and Smith 1983) and the optimum range (13-22) for benthic microalgae (Hillebrand and Sommer 1999). The higher N : P ratios recorded in the present study are not unusual for nitrogen-fixing species, which have often been documented as having higher N : P stoichiometry than non-diazotrophic species (Table 4).…”
Section: Tissue Nutrient Content and Changescontrasting
confidence: 41%
See 2 more Smart Citations
“…8b) in the current study are similar to ratios (46-51) reported from Deception Bay in 2005 but are higher than the ratio (14) reported for Deception Bay in 1999-2000 (Watkinson et al 2005) and the Eastern Banks (16.4-22.4) (Ahern et al 2007). The N : P ratios reported in the present study, particularly during the incipient, rapid growth and plateau phases (47-72), were substantially higher than the various optimum N : P ranges published in the literature, including optimum ratios for unicellular phytoplankton (16) (Redfield et al 1963), freshwater periphyton (18) (Hecky et al 1993), medium ratio (30) for benthic plants (Atkinson and Smith 1983) and the optimum range (13-22) for benthic microalgae (Hillebrand and Sommer 1999). The higher N : P ratios recorded in the present study are not unusual for nitrogen-fixing species, which have often been documented as having higher N : P stoichiometry than non-diazotrophic species (Table 4).…”
Section: Tissue Nutrient Content and Changescontrasting
confidence: 41%
“…8a). These ratios were at the higher end of the optimum range (5-10) for marine microalgae (Hillebrand and Sommer 1999) and much higher than the Redfield stoichiometry (6.6) for unicellular phytoplankton (Redfield et al 1963), or for the optimum ratio (8.8) for freshwater periphyton (Kahlert 1998). The higher C : N ratios of L. majuscula recorded in the current study are consistent with data from previous studies in Deception Bay: 9.8-10.4 in 2005 and 12.8 in 1999-2000 (Watkinson et al 2005) and in eastern Moreton Bay (8.8-9.4; Ahern et al 2007).…”
Section: Tissue Nutrient Content and Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…O conteúdo de nitrogênio e fósforo e a razão N:P da massa perifítica têm sido usados com sucesso para indicação do potencial de limitação nutricional do perifíton (Biggs 1995, Borchardt 1996, Hillebrand & Sommer 1999. Trabalhos mais abrangentes, em escala espacial, utilizaram a o estado nutricional do perifíton para comparar o potencial de limitação algal entre ecossistemas, a exemplo de Maberly et al (2002) e Francouer et al (1999, os quais compararam 30 lagos e 12 rios de regiões temperadas, respectivamente.…”
Section: Discussionunclassified
“…This difference could be related to the large concentration of protein in AFA or to an optimal growth rate of AFA. Benthic algae (including cyanophytes) have been reported to produce C:N ratios that decreased with increasing growth rate (Hillebrand and Sommer, 1999).…”
Section: Carbon and Nitrogen Analysesmentioning
confidence: 99%